FDZ data description: Real-estate data for Germany (RWI-GEO-RED v7) - Advertisements on the internet platform lmmobilienScout24 2007-06/2022 - Sandra Schaffner; Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
The FDZ Ruhr provides a dataset on real estate advertisements in Germany from 2007 onwards. The data are based on information from the internet platform ImmobilienScout24 and covers both apartments and houses for sale and for rent. The data are available for scientific research only. The provided dataset covers detailed regional information and a rich set of housing charac-teristics. This data report gives a brief overview on the data as well as its limitations and specifics. The data report is addressed to (potential) users of the data as support for their data preparation. This data report refers to RWI-GEO-RED v7 that covers data until June 2022. – – Das FDZ Ruhr stellt einen Datensatz zu Immobilienanzeigen in Deutschland ab dem Jahr 2007 zur Verfügung. Die Daten beruhen auf Informationen der Internetplattform ImmobilienScout24 und umfassen sowohl Wohnungen als auch Häuser zum Kauf und zur Miete. Die Daten stehen ausschließlich für die wissenschaftliche Forschung zur Verfügung. Der bereitgestellte Datensatz enthält detaillierte regionale Informationen und eine Vielzahl von Wohnungsmerkmalen. Diese Datenbeschreibung gibt einen kurzen Überblick über die Daten sowie über ihre Grenzen und Besonderheiten. Diese Datenbeschreibung richtet sich an (potenzielle) Nutzende der Daten als Unterstützung für deren Datenaufbereitung. Diese Datenbeschreibung bezieht sich auf RWI-GEO-RED v7, die Version umfasst Daten bis Juni 2022.
Keywords: 330